The European debt crisis and fiscal reaction functions in Europe 2000 - 2012 - Guido Baldi; Karsten Staehr (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
After the global financial crisis, some governments in the EU experienced serious debt financing problems, while others were less affected. This paper seeks to shed light on the divergent fiscal performance by assessing the fiscal conduct in the EU countries before and after the outbreak of the crisis. Fiscal reaction functions of the primary balance are estimated for different groups of EU countries using quarterly data for the pre-crisis period 2001-2008 and for the post-crisis period 2009-2012. The pre-crisis estimations reveal some differences in persistence and cyclical reaction between different groups of countries, but generally little feedback from the debt stock to the primary balance. The countries that eventually developed fiscal problems do not stand out. The post-crisis estimations show less counter-cyclicality and much more feedback from the debt stock, and these reactions are particularly pronounced for the countries with severe fiscal problems.
Keywords: E61; E62; H62; H63; 330; fiscal reaction function; global financial crisis; debt crisis; structural break